Effect of the application of curcumin (Curcuma Longa) oral gel on periodontal inflammation in patients with type 2 diabetes melitus - Nur Rahman Ahmad Seno Aji; Vincensia Maria Karina; Osa Amila Hafiyyah; Kwartarini Murdiastuti; Ahmad Syaify (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
Patients with Type 2 Diabetes mellitus (T2DM) were more prone to suffer from periodontitis due to unique alteration in host immune response. Application of curcumin oral gel as adjunctive therapy was expected to improve periodontal condition due to its anti-inflammatory properties. The objective of this study was to evaluate the effect of curcumin oral gel on periodontal inflammation in patients with T2DM. Sixteen periodontal pockets (n=16) from patients with T2DM were administered with curcumin oral gel using blunt cannula after periodontal curettage. Gingival Index (GI) and Periodontal Pocket Probing Depth (PPD) were evaluated a month after application. GI was assessed using visible sign of inflammation parameters including swelling, redness and bleeding upon probing. PPD was assessed using UNC-15 periodontal probe. The results were analyzed by Wilcoxon test (two related samples). The results showed that GI before treatment decreased by 51.61% a month post application. There was statistically significant difference (Sig 0.003) between GI mean before and after curcumin application. PPD decreased by 42.81% and showed statistically significant difference (Sig 0.000) by Wilcoxon Test. It is concluded that application of curcumin oral gel post curettage could decrease periodontal inflammation in patients with T2DM.